Analysis of Genetic Diversity and Population Structure of Orobanche foetida Populations From Tunisia Using RADseq - Boukteb, Amal; Sakaguchi, Shota; Ichihashi, Yasunori; Kharrat, Mohamed; Nagano, Atsushi J.; Shirasu, Ken; Bouhadida, Mariem (Frontiers in Plant Science, 2021)
Orobanche foetida Poiret is a holoparasitic plant that lacks chlorophyll and totally depending on its host for its growth. Orobanche foetida parasitizes host plant roots and extract nutrient and water via a haustorium. Although O. foetida distributes in the Mediterranean region as a wild plant parasite, it parasitizes faba bean causing serious damages which may reach 90 % yield losses in Tunisia. Analysis of genetic diversity of the parasite is important to better understand its evolution and spread, remained largely unknown. In this work, we present the first study on genetic diversity and population structure using the robust technique Restriction‐site‐Associated DNA sequencing (RADseq) for Orobanche spp. We collected 244 samples of O. foetida from 18 faba bean fields in the north of Tunisia including 17 populations from the north-west and one population form the north-east. To overcome the difficulty of SNP discovery in O. foetida genome as a non-model and tetraploid plant, we utilized three different informatics pipelines, namely UNEAK, pyRAD and Stacks. This study showed that genetic differentiation has been occurred in the Tunisian O. foetida emphasizing the isolation by distance effect. However, no strong population clustering was detected in this work basing on the three data sets and clustering methods used. The present study shed the light on the current distribution and the genetic variation situation of the fetid broomrape in Tunisia, highlighting the importance of understanding the evolution of this parasite and its genetic background. This will aid in developing efficient strategies to control this parasite and its expansion in Tunisia and worldwide.